An advanced optical clearing protocol allows label-free detection of tissue necrosis via multiphoton microscopy in injured whole muscle - Schneidereit, Dominik; Broellochs, Anita; Ritter, Paul; Kreiß, Lucas; Mokhtari, Zeinab; Beilhack, Andreas; Krönke, Gerhard; Ackermann, Jochen; Faas, Maria; Grüneboom, Anika; Schürmann, Sebastian; Friedrich, Oliver (Theranostics, 2021)
Rationale: Structural remodeling or damage as a result of disease or injury is often not evenly distributed throughout a tissue but strongly depends on localization and extent of damaging stimuli. Skeletal muscle as a mechanically active organ can express signs of local or even systemic myopathic damage, necrosis, or repair. Conventionally, muscle biopsies (patients) or whole muscles (animal models) are mechanically sliced and stained to assess structural alterations histologically. Three-dimensional tissue information can be obtained by applying deep imaging modalities, e.g. multiphoton or light-sheet microscopy. Chemical clearing approaches reduce scattering, e.g. through matching refractive tissue indices, to overcome optical penetration depth limits in thick tissues.
CRIS-Team WoS Importer:2021-01-22

Formation of atherosclerotic lesions is independent of eosinophils in male mice - Hofheinz, Katharina; Seibert, Fabian; Ackermann, Jochen; Dietel, Barbara; Tauchi, Miyuki; Oszvar-Kozma, Maria; Kühn, Hartmut; Schett, Georg; Binder, Christoph J.; Krönke, Gerhard (Atherosclerosis, 2020)
Background and aims: Oxidation of low-density lipoprotein (LDL) and oxidized LDL-mediated activation of the innate immune system have been recognized as early key events during the pathogenesis of atherosclerosis. Recent evidence identified eosinophils as a major source of enzymatic lipid oxidation and suggested a potential role of type 2 immunity in atherogenesis. However, the involvement of individual type 2 immune cell subsets involved in this process has been incompletely defined. We therefore sought to determine the role of eosinophils during LDL oxidation and the pathogenesis of this disease. Methods: Using eosinophil-deficient dblGATA1 mice, we studied the role of eosinophils in two established mouse models of atherosclerosis. Results: These experiments revealed that the presence of eosinophils did neither affect biomarkers of LDL oxidation nor atherosclerotic lesion development. Conclusions: The obtained results show that LDL oxidation and development of atherosclerosis are largely independent of eosinophils or eosinophil-mediated LDL oxidation.
CRIS-Team Scopus Importer:2020-09-25
Keywords: Atherosclerosis; Eosinophils; Lipid oxidation

IL-33-induced metabolic reprogramming controls the differentiation of alternatively activated macrophages and the resolution of inflammation - Faas, Maria; Ipseiz, Natacha; Ackermann, Jochen; Culemann, Stephan; Grüneboom, Anika; Schröder, Fenja; Rothe, Tobias; Scholtysek, Carina; Eberhardt, Martin; Böttcher, Martin; Kirchner, Philipp; Stoll, Cornelia; et al. (Immunity, 2021)
Alternatively activated macrophages (AAMs) contribute to the resolution of inflammation and tissue repair. However, molecular pathways that govern their differentiation have remained incompletely understood. Here, we show that uncoupling protein-2-mediated mitochondrial reprogramming and the transcription factor GATA3 specifically controlled the differentiation of pro-resolving AAMs in response to the alarmin IL-33. In macrophages, IL-33 sequentially triggered early expression of pro-inflammatory genes and subsequent differentiation into AAMs. Global analysis of underlying signaling events revealed that IL-33 induced a rapid metabolic rewiring of macrophages that involved uncoupling of the respiratory chain and increased production of the metabolite itaconate, which subsequently triggered a GATA3-mediated AAM polarization. Conditional deletion of GATA3 in mononuclear phagocytes accordingly abrogated IL-33-induced differentiation of AAMs and tissue repair upon muscle injury. Our data thus identify an IL-4-independent and GATA3-dependent pathway in mononuclear phagocytes that results from mitochondrial rewiring and controls macrophage plasticity and the resolution of inflammation.
CRIS-Team Scopus Importer:2021-11-19
Keywords: alternatively activated macrophage; GATA3; interleukin-33; itaconate; mitochondrial rewiring; resolution of inlammation; UCP2; uncoupling

Stunning of neutrophils accounts for the anti-inflammatory effects of clodronate liposomes - Culemann, Stephan; Knab, Katharina; Euler, Maximilien; Wegner, Anja; Garibagaoglu, Hilal; Ackermann, Jochen; Fischer, Kim; Kienhoefer, Deborah; Crainiciuc, Georgiana; Hahn, Jonas; Grüneboom, Anika; Nimmerjahn, Falk; et al. (Journal of Experimental Medicine, 2023)
The authors show that the anti-inflammatory effects of clodronate liposomes do not result from the depletion of mononuclear phagocytes but from a functional stunning of polymorphonuclear neutrophils. These findings necessitate a critical revision of the current literature on the role of monocytes and macrophages in inflammation.
CRIS-Team WoS Importer:2023-04-28